2015
DOI: 10.5121/ijsea.2015.6108
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility: A Key Factor to Testability

Abstract: Testability is an important software quality factor that is ineffective if it is not available at an early stage in the development life-cycle. It becomes more essential in the case of object oriented design. Flexibility is an important key factor to testability analysis and measurement for delivering high class testable and maintainable software. Flexibility is a criterion of crucial significance to software developers, designers and the quality controllers. It constantly guides and supports to avoid wastage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 12 publications
(13 reference statements)
0
29
0
1
Order By: Relevance
“…Bohem found that among 60% to 70% of all the faults detected in large level projects was either specification or design faults [14]. A decision to modify the design in order to recover testability after coding has started may be extremely expensive and error-prone [4]. The target of increasing the testability of object oriented design is not only to detect defects but more significantly, to detect defects as quickly as they are occurred.…”
Section: Testability Measurement At Design Phasementioning
confidence: 99%
See 3 more Smart Citations
“…Bohem found that among 60% to 70% of all the faults detected in large level projects was either specification or design faults [14]. A decision to modify the design in order to recover testability after coding has started may be extremely expensive and error-prone [4]. The target of increasing the testability of object oriented design is not only to detect defects but more significantly, to detect defects as quickly as they are occurred.…”
Section: Testability Measurement At Design Phasementioning
confidence: 99%
“…Correlation phase in framework correlated the identified testability factors with OO design properties. A regression line will be established to measure testability factors in terms of design characteristics with the help of design metrics [4]. 5.…”
Section: Too Late To Improve Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Reuse eventually saves us time and money, and will ultimately lead to a more stable and reliable product [22][23][24][25]. …”
Section: Software Reusabilitymentioning
confidence: 99%